Brain reserve against physical disability progression over 5 years in multiple sclerosis. (24th May 2016) - Sumowski, James F.; Rocca, Maria A.; Leavitt, Victoria M.; Meani, Alessandro; Mesaros, Sarlota; Drulovic, Jelena; Preziosa, Paolo; Habeck, Christian G.; Filippi, Massimo
Abstract : Objective: The brain reserve hypothesis links larger maximal lifetime brain growth (MLBG, estimated with intracranial volume [ICV]) with lower risk for cognitive decline/dementia. We examined whether larger MLBG is also linked to less physical disability progression over 5 years in a prospective sample of treatment-naive patients with multiple sclerosis (MS). Methods: Physical disability was measured with the Expanded Disability Status Scale (EDSS) at baseline and 5-year follow-up in 52 treatment-naive Serbian patients with MS. MRI measured disease burden (cerebral atrophy, T2 lesion volume) and MLBG: a genetically determined, premorbid (established during adolescence, stable thereafter) patient characteristic estimated with ICV (adjusted for sex). Logistic regression tested whether MLBG (smaller vs larger) predicts disability progression (stable vs worsened) independently of disease burden. Results: Disability progression was observed in 29 (55.8%) patients. Larger MLBG predicted lower risk for progression (odds ratio 0.13, 95% confidence interval 0.02–0.78), independently of disease burden. We also calculated absolute change in EDSS scores, and observed that patients with smaller MLBG showed worse EDSS change (0.91 ± 0.71) than patients with larger MLBG (0.42 ± 0.87). Conclusions: Larger MLBG was linked to lower risk for disability progression in patients with MS over 5 years, which is the first extension of the brain reserve hypothesis to physical disability. MLBG (ICV) represents a clinically available metric that may help gauge risk for future disability in patients with MS, which may advance the science and practice of early intervention. Potential avenues for future research are discussed.